Adolescents Mental Health During Covid-19 Pandemic - Elysa Dwi Sitohang (JOURNAL OF BAJA HEALTH SCIENCE, 2023)
Since the end of 2019, people in various countries, including Indonesia has experience the Covid-19 pandemic. The measures to prevent the spread of the Covid-19 from the government limited people’s physical activity. In education, the policies leads to the implementation of Online Distance Learning for students ranging from elementary school to higher education levels. The purpose of this study was to obtain an overview of the mental health of adolescents during the Covid-19 pandemic and to identify sociodemographic factors that influence adolescent mental health. The study involved 205 participants aged 15-18 years. The data were collected using a validated General Health Questionnaire (GHQ-12) self-assessment measurement tool in Indonesian language adapted version. The results showed that 59.5% of adolescents experienced psychological problems in the form of psychological distress and social dysfunction. Girls and adolescents who experience changes in sleep hours have a greater tendency to experience psychological problems. So that during the pandemic, teenage girls need more attention than boys. In addition, sleep patterns also need to be considered to reduce impact on psychological distress and social dysfunction during the pandemic.